Mengelola Sampah, Menjaga Desa: Strategi Optimalisasi Sampah Rumah Tangga Menuju SDG’s - Arief Yulianto; Wahyono Wahyono; Vini Wiratno Putri; Fredianaika Istanti; Erisa Aprilia Wicaksari (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service program aims to educate village residents on the importance of waste separation and processing, implement simple circular economy-based technologies, and establish a community-based waste management system. A participatory approach is carried out through awareness campaigns and training on household-level waste sorting, environmental campaigns through schools, communities, and social media, as well as incentive programs for residents actively involved in waste management, such as waste bank initiatives. The outcomes of this program are expected to create a cleaner and healthier village environment, improve the community’s economic well-being, and support the achievement of the Sustainable Development Goals (SDGs). Furthermore, the program is intended to serve as a replicable model for waste management in other regions with similar characteristics.